Superoxide dismutase and glutathione peroxidase in oral submucous fibrosis, oral leukoplakia, and oral cancer: A comparative study - Shubha Gurudath; Raghavendra Mahadev Naik; K S Ganapathy; Yadavalli Guruprasad; D Sujatha; Anuradha Pai (Wolters Kluwer Medknow Publications, 2012)
Objectives: Present study was undertaken to estimate and compare erythrocyte superoxide dismutase (E-SOD) and glutathione peroxidase (GPx) levels in oral submucous fibrosis, oral leukoplakia, oral cancer patients, and healthy subjects. Materials and Methods: E-SOD and GPx levels were estimated in OSF, oral leukoplakia, and oral cancer patients with 25 subjects in each group. The results obtained were compared with the corresponding age-/sex- matched control groups. Results: Statistically significant ( P < 0.001) decrease in E-SOD and GPx levels were observed in OSF, oral leukoplakia, and oral cancer groups as compared to the control group. Oral leukoplakia group showed lower levels in comparison with OSF ( P > 0.05). Oral cancer group had the lowest levels amongst the study groups. Conclusion: Imbalance in antioxidant enzyme status may be considered as one of the factors responsible for the pathogenesis of cancer and may serve as a potential biomarker and therapeutic target to reduce the malignant transformation in oral premalignant lesions/conditions.